Islamic Boarding School Linguistic Landscape in The Development of Arabic Language Skills and Islamic Knowledge - Sofyan, Akhmad; Bayu Firmansyah, Mochamad; Muta’allim, Muta’allim; Markiano Solissa, Everhard; Rosikh, Fahrur (International Journal of Educational Research & Social Sciences, 2022)
Linguistic landscape is one area of ​​sociolinguistics that examines specifically the phenomenon of language use in public spaces, be it monolingual, bilingual or multilingual. Islamic boarding schools as geographically exclusive Islamic educational institutions have a linguistic landscape phenomenon that is characterized and based on Arabic. This is in line with the Islamic orientation built in pesantren education. This study aims to explore the use of Arabic in the public space of Islamic boarding schools and its contribution to the development of Arabic language skills and Islamic knowledge of students. This research is a qualitative research with descriptive analysis. In this study, data collection used the observing method and the documentation method. The listening method is used to collect data in the form of writing while the documentation method is used to collect data in the form of pictures taken by cell phone. All data is processed and given a code and then selected based on who produced the text. The results of this study are: (1) The linguistic landscape of Arabic in the pesantren environment is categorized into 3 categories: verses of the Qur'an, Matan Hadith Nabawi, and Maqolah of Ulama. (2) The linguistic landscape of Arabic is part of the pesantren learning process indirectly, especially in supporting classroom learning so that it is internalized in life. (3) The linguistic landscape of Arabic has significance in developing the Arabic language skills and Islamic knowledge of the students in the pesantren environment.